Effect of organic acid, biofertilizers and two mycorrhiza species in the rootstock on some germination characteristics and seedling growth of Iranian ox-tongue (Echium amoenum Fisch & Mey.) - mohammad behzad amiri; Parviz Rezvani Moghaddam; Mohsen Jahan (علوم و فناوری بذر ایران, 2021)
An experiment based on CRD design with three replications was conducted in 2014 year, in Ferdowsi University of Mashhad, Iran. The experimental treatments included 7 types of eco-friendly inputs: Humic acid, Fulvic acid, Nitroxin (contains Azotobacter spp. And Azospirillum spp. Bacterias), Biophosphorous (contains Bacillus sp. And Pseudomonas sp. bacterias), Biosulfur (contains Thiobacillus spp. Bacteria), Glomus mosseae, Glomus intraradices, and control. The results showed that organic acids of humic and fulvic increased germination percentage 25 and 20% and germination rate 58 and 33% compared to control, respectively. Germination percentage was 20, 25, and 24% more in biofertilizers of nitroxin, biophosphorous and biosulfur compared to control, respectively and germination rate under application of this fertilizers added 59, 24, and 50% compared to control, respectively. Humic acid, fulvic acid, nitroxin, biophosphorous, biosulfur, Glomus mosseae and Glomus intraradices reduced mean germination time 33, 35, 38, 19, 36, 36, and 16% compared to control, respectively. The highest radicle and plumule length obtained in treatment of humic acid and the highest radicle to plumule length observed in treatment of biosulfur. Fulvic acid increased radicle and plumule dry weight 51 and 38% compared to control, respectively. The highest and the lowest radicle to plumule dry weight obtained in treatments of Glomus intraradices (0.199) and control (0.124), respectively.